Bipolar affective disorders in epilepsy - G. E. Mazo; L. V. Lipatova; N. E. Zhukov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The relationship between bipolar affective disorders (BAD) and epilepsy have an obvious comorbidity, similar theoretical bases of pathogenesis and treatment approaches. In both diseases, there is a high risk of suicide without treatment, the frequency of episodes of BAD increases, and the lucid intervals become shorter, the progression of the disease is similar to one as for epilepsy. Discusses general pathophysiological mechanisms of epilepsy and BAD and treatment of affective disorders of the bipolar spectrum in patients with epilepsy.